Gambaran Kompetensi Budaya pada Mahasiswa Keperawatan dan Perawat: Overview of Cultural Competence in Nursing Students and Nurses - Angeli Helmina Vintauli Br.R; Enjelika Ria Manalu; Karina Bevelyn Panjaitan; Eva Chris Veronica Gultom; Martha Octaria (Fakultas Keperawatan Universitas Andalas, 2024)
Culture is still considered less important than other components in patient care, especially patients with critical conditions. This lack of knowledge of cultural competence in nursing among nurses and nursing students will have an impact on the nursing care provided to patients. The process of providing nursing services requires every nurse to have an understanding of cultural competence. To identify the level of cultural competence in nursing students and nurses. This study used descriptive quantitative methods with a cross-sectional approach. The research sample amounted to 204 respondents in nursing students and 109 respondents in nurses. The questionnaire was tested for validity with the Nursing Cultural Competence Scale (NCCS). The instrument has been tested for validity and reliability. Student respondents had cultural competence in the low category (55.9%), and nurse respondents had cultural competence in the low category (53.2%). Cultural competence in students and nurses needs to be improved by the existence of evaluation materials in mandatory teaching subjects regarding transcultural in educational institutions, special training programs or seminars for nurses in hospitals, and can develop research related to factors that affect cultural competence in nursing.